2018
DOI: 10.1002/ase.1795
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anatomy Computer‐Assisted Learning on Spatial Abilities of Medical Students

Abstract: Currently, medical education context poses different challenges to anatomy, contributing to the introduction of new pedagogical approaches, such as computer-assisted learning (CAL). This approach provides insight into students' learning profiles and skills that enhance anatomy knowledge acquisition. To understand the influence of anatomy CAL on spatial abilities, a study was conducted. A total of 671 medical students attending Musculoskeletal (MA) and Cardiovascular Anatomy (CA) courses, were allocated to one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
10

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 81 publications
(143 reference statements)
2
20
0
10
Order By: Relevance
“…For example, studies showing that handling physical specimens had major positive impact on learning for certain students which was not seen when a commercial e‐learning tool was used (Van Nuland and Rogers, 2017). Meanwhile, questions could be raised on whether some of this knowledge could be taught using CAL after being introduced as part of the curriculum (Guimarães et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, studies showing that handling physical specimens had major positive impact on learning for certain students which was not seen when a commercial e‐learning tool was used (Van Nuland and Rogers, 2017). Meanwhile, questions could be raised on whether some of this knowledge could be taught using CAL after being introduced as part of the curriculum (Guimarães et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that expert clinical anatomists were better in performing metric spatial tasks than novices, suggesting that visual‐spatial abilities are trained by practice and education. In addition, the dose‐dependent effect of practice and learning on visual‐spatial abilities has been found in medical undergraduates after attending CAL courses of musculoskeletal and cardiovascular anatomy (Guimarães et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Dados sobre a aprendizagem por computador demonstrou que houve uma melhora dependente da dose, ou seja, quanto maior a quantidade de treinamento através dessa tecnologia, maior foi o desempenho das habilidades espaciais pelos estudantes 21 .…”
Section: Discussionunclassified